Industrial training programme to continue despite review on ECRL - Siti Nur Azwin, Zulkapri (Sun Media Corporation Sdn Bhd, 2018)
Kuala Lumpur: The East Coast Rail Link Industrial Skills Training Programme (PLKI-ECRL) will continue despite the proposal for the government to review the ECRL project.